(untitled) (International Journal of Architecture and Urbanism, 2023)
One factor that influences public health is the quality of the health of the residential environment, which is determined by the quality of the green open space. The role of green open space in housing is to make residents who stay inside feel like being in nature, not like in a crowded room, to improve the psychological health of residents. This study aims to explore condominium designs that have good oxygen levels, avoid air pollution and inhibit the spread of the virus so that the condominium can improve the physical health of residents. The method used descriptive qualitative in the form of a literature study. The results of this study produce healthy building designs with natural lighting and ventilation in housing that saves energy use, cool air humidity, a building site that is free from air pollution and noise by vehicles, reusable water quality, residential safety, green open space that can provide good oxygen levels, and green open space that connected to the indoor area.